COMMON ERRORS IN ENGLISH VERB TENSE SHIFT MADE BY ENGLISH SPECIALIZING TENTH-GRADERS AT THAI BINH SPECIALIZING HIGH SCHOOL - Nguyễn, Thị Hòa (2021)
Verb tense and tense shift play an important role in the mastery of English language. The aim of this research was to identify the common tense shift errors that the students make when doing verb tense exercises and the causes for those errors, some suggestions to minimize the errors were elicited as well. The participants included 65 English-specializing 10th-graders and their two English teachers at Thai Binh Specializing High School. The study adopted a mixed design with three data collection instruments which were tests, questionnaires and semi-structured interviews to find the answers to the two research questions.In answering the first research question about common errors found in students’ exercises, the most surprisingly problematic tense was simple future, followed by perfect tenses. The shifting of simple present and past progressive tenses caused just few difficulties to the students. Besides, for all types of errors, students performed much better in the multiple choice than the simple completion tests. As for the second question about the causes for those errors, students’ inappropriate learning strategies proved to be the most dominant one, which together with the ineffective teaching of some secondary school teachers, made it more likely that students would use verb tense shift incorrectly. The lack of study materials and the wide application of MC also had certain influence on the errors. It was also reported that Vietnamese and spoken language had little effect on students’ incorrect use of verb shift. Based on those findings, the study also offered some ways to minimize the errors and suggestions for further research